The structure transformation of pre‐oriented polylactic acid film during uniaxial stretching at room temperature. Issue 3 (22nd May 2019) - Xu, Rui‐Jie; Tian, Zi‐Qin; Xie, Jia‐Yi; Lei, Cai‐Hong
Abstract: In this article, the pre‐oriented polylactide (PLA) films were prepared by extrusion casting under melt‐stretching flow and cast roll temperature field. Shish‐kebab like structure was induced and the elongation at break under room temperature of PLA film prepared with melt‐draw ratio of 40 was high to 270%. To clarify the origin of this ductile behavior, the pre‐oriented PLA structure evolution during stretching at room temperature was followed. It was found that melt‐stretching makes the chains fully extended to form amount of rigid amorphous fraction (RAF). The low chain entanglement induces weak connection strength between RAF and mobile amorphous fraction. The craze is easily formed at the interface between these two phases. The initial ductile deformation during stretching of pre‐oriented PLA films comes from the rigid extended chain slip and free amorphous chain network deformation. When the strain is higher than 40%, the RAF region appears periodic ordered structure. With the strain increasing, the RAF gradually transforms to mesophase. The molecular chains are stretched to extend in the crazes. The strain‐hardening behavior comes from the crystal destroy and chain extension. The room temperature stretching of pre‐oriented PLA film can only increase chain's orientation and package tightness, but could not induce the formation of highly perfect crystals. Abstract : The room temperature stretching of pre‐oriented PLA film can only increase rigid amorphous fraction (RAF) transformation to mesophase rather than to highly perfect crystals.